Peningkatan Sifat-Sifat Fatik Baja NS-1045 Chromized dengan Proses Perlakuan Panas - Amru Siregar; , Amrinsyah (Jurnal Teknik Mesin (Sinta 3), 2013)
Metal alloys for usage the high temperature, besides needed the good mechanical properties, also needed the corrosion resistance properties. Chromized components exhibit superior resistance to a variety of aggressive corrosive mechanism, including high temperature oxidation, and chloride-related attack. Chromized coatings are diffusion-type coating can be applied by electrodeposition. So that happened degradation fatigue strength of chromized steel. The mechanical properties of chromized steel can be improved by heat-treatment process. In this research conducted hardening and tempering process to NS-1045 chromized steel. Influence of heat-treatment to the mechanical properties, it is has been tested by using machine rotary bending test. While examination of microstructure can do it by using microscope optic and scanning electrone microscopy (SEM). Analysis influence heat-treatment of NS-1045 chromized steel to fatigue strength, it is increase about (20÷25)%.